ANALYZING PLATFORM POWER IN THE CULTURAL INDUSTRIES - Nieborg, David B.; Poell, Thomas; Duffy, Brooke Erin (AoIR Selected Papers of Internet Research, 2021)
Across cultures and contexts, digital platforms like YouTube, TikTok/Douyin, WeChat, and Spotify are fundamentally reshaping both the processes and products of cultural production—from music and news to entertainment and advertising. But, despite considerable attention to the perverse power of algorithms in various spheres of social and economic life, we contend that existing political economic frameworks fail to account for the distinctiveness of the cultural industries. Challenging essentialist theories of platform dominance, this paper argues that claims of platform power need to be qualified in the context of industry- and culture-specific inquiries. Building on research in science and technology studies (STS), software studies, political economy, business studies, and media industries studies, the paper presents a new analytical framework to analyse the evolving power relationship between platforms and cultural producers. It is argued that the decision space of cultural producers in their role as platform complementors is shaped by three key variables: 1) platform evolution, 2) cultural industry segments, and 3) stages of production. The proposed framework makes clear that, while the relationship between platforms and cultural producers is staggeringly uneven and, at times, highly volatile, it should be understood as one of mutual dependence. That is, platforms exert mechanisms of power over the phases of the creation, distribution, monetization, and marketing of culture; but they also furnish space for negotiation and contestation. Acknowledging this requires a framework that is less deterministic and sensitive to the nuance inherent in cultural production.